2017
DOI: 10.1111/jocn.14115
|View full text |Cite
|
Sign up to set email alerts
|

Does an intervention designed to improve self‐management, social support and awareness of palliative‐care address needs of persons with heart failure, family caregivers and clinicians?

Abstract: These findings add to the growing evidence of the feasibility and acceptability of programs that address care values and preferences, and care planning. The iSCIP can be used as a guide for developing interventions and software applications, which involve both partners in care and palliative-care discussions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 34 publications
0
21
0
Order By: Relevance
“…However, only a few studies have adopted homebased self-management psychosocial education intervention with the integration of mHealth for patients with CHF. 37,38 The results from the current pilot testing showed that the HOM-HEMP was feasible and potentially effective in improving patient's self-care management, psychological outcomes and HRQoL.…”
Section: Discussionmentioning
confidence: 89%
“…However, only a few studies have adopted homebased self-management psychosocial education intervention with the integration of mHealth for patients with CHF. 37,38 The results from the current pilot testing showed that the HOM-HEMP was feasible and potentially effective in improving patient's self-care management, psychological outcomes and HRQoL.…”
Section: Discussionmentioning
confidence: 89%
“…Most of the articles reviewed included populations inhabiting developed countries, apart from one that focused on a developing country (South Africa). Most of these qualitative studies focused on the United States [21,23-25,27,31,34,36,41,43,45,47,48,54] and the United Kingdom [30,32,35,42,53,61]. Other countries included were the Netherlands [22,33,44], Denmark [26,55,58], Sweden [38,40,49], Australia [28,29,46], Canada [50,56], South Africa [62], Singapore [59], China [63], Germany [37], Ireland [57], Belgium [60], Spain [39], and Switzerland [52].…”
Section: Resultsmentioning
confidence: 99%
“…Most of the apps under consideration were tailored to deal with chronic diseases: cancer [22,30,33,38,40,56,63]; HIV [23,24,31,45,48]; diabetes [28,50,55]; hypertension and cardiovascular diseases [43,54,57]; chronic kidney disease [27,42]; cystic fibrosis [21,51]; chronic pain [26,58]; juvenile arthritis [35,61]; brain and spinal cord anomalies [34]; multiple sclerosis [52]; chronic illnesses, in general [25,62]; and mental health disorders [32,36,39,41,46,47,53,60]. Other apps were specific to pregnancy/obstetric care [29,37,44,59], and one was for postoperative care [49].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Shared care consisted of 3 components, including communication, decision‐making and reciprocity 10 . The relationship of SCM elements and individual self‐care, self‐efficacy, quality of dyadic relationship and emotional well‐being of patients with heart disease has been well evidenced in research 10,19,22 . SCM‐based interventions have also shown significant positive effects on patients' self‐care, quality of life and dyadic relationship in the case of chronic illness 19,22 .…”
Section: Methodsmentioning
confidence: 99%